2017
DOI: 10.5935/abc.20170151
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac, Metabolic and Molecular Profiles of Sedentary Rats in the Initial Moment of Obesity

Abstract: BackgroundDifferent types of high-fat and/or high-energy diets have been used to induce obesity in rodents. However, few studies have reported on the effects observed at the initial stage of obesity induced by high-fat feeding on cardiac functional and structural remodelling.ObjectiveTo characterize the initial moment of obesity and investigate both metabolic and cardiac parameters. In addition, the role of Ca2+ handling in short-term exposure to obesity was verified.MethodsThirty-day-old male Wistar rats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(34 reference statements)
0
2
0
1
Order By: Relevance
“…7,[12][13][14] However, there are important divergences among studies regarding potential effects of high-fat diet induced obesity on myocardial performance. Jacobsen et al 15 found increased contractile phase during inotropic maneuver of papillary muscle in obese rats after three weeks of diet; other authors have found higher myocardial shortening velocity in experiments of 20, 8 30, 11 33, 13 and 35 weeks. 16 Other investigations have reported impaired cardiac contraction, showed by in vitro papillary muscles analysis of obese rats in experimental models with15 weeks of diet.…”
Section: Introductionmentioning
confidence: 93%
“…7,[12][13][14] However, there are important divergences among studies regarding potential effects of high-fat diet induced obesity on myocardial performance. Jacobsen et al 15 found increased contractile phase during inotropic maneuver of papillary muscle in obese rats after three weeks of diet; other authors have found higher myocardial shortening velocity in experiments of 20, 8 30, 11 33, 13 and 35 weeks. 16 Other investigations have reported impaired cardiac contraction, showed by in vitro papillary muscles analysis of obese rats in experimental models with15 weeks of diet.…”
Section: Introductionmentioning
confidence: 93%
“…O índice de adiposidade (IA) post-mortem foi calculado utilizando a fórmula: IA = [gordura corporal/peso corporal] x 100. A gordura corporal (g) foi calculada pela soma dos seguintes constituintes do tecido adiposo: gordura perigonadal + gordura retroperitoneal + gordura mesentérica (Jacobsen et al, 2017).…”
Section: Avaliação Da Obesidadeunclassified
“…The sample size used in this study was based on the literature and on our previous studies. 13,[17][18][19] The control group was fed standard rat chow (RC Focus 1765, Agroceres ® , Rio Claro, SP, Brazil) containing 12.3% of kilocalories from fat, 57.9% from carbohydrates, and 29.8% from protein, whereas the obese group was fed one of four alternating high-fat diets (RC Focus 2413, 2414, 2415, and 2416, Agroceres ® , Rio Claro, SP, Brazil) containing 49.2% of kilocalories from fat, 28.9% from carbohydrates, and 21.9% from protein. The four high-fat diets had the same nutritional composition, except flavoring additives, namely, cheese, bacon, chocolate, or vanilla.…”
Section: Animals and Experimental Protocolmentioning
confidence: 99%